The priesthood of believers : a critical analysis and evaluation of developments in the Ecclesiology of the Seventh-Day Adventist Church - Sokupa, Mxolisi Michael (Stellenbosch : Stellenbosch University, 2011)
Thesis (DTh)--Stellenbosch University, 2011.